Illumina : Implantation d’un projet de recherche-action et de création participative dans le champ de la santé mentale - Saillant, Francine (Anthropologica, 2025)
This article is based on an experiment conducted in 2022-2023 in a mixed-use neighborhood struggling with homelessness. This neighborhood is home to numerous community and cultural organizations, including Sherpa, with which the Illumina project was initiated. This creative and artistic project, set up in collaboration with anthropological researchers, stakeholders and artists, is being implemented throughout the neighborhood. Creation and art have had several functions: as an alternative form of relationship with the individuals who frequent community organizations, primarily those concerned with mental health. Among other things, Illumina led to the creation of a public art trail, the result of some fifty collective workshops involving 200 participants. This article offers both a synthesis of this initiative and a critical reflection on the themes of stigma, precariousness, narrativity and methodologies.